Prevalence and Profile of Tapentadol Use in Patients Visiting a Drug De-addiction Center in Kashmir - Syed Mehvish; Heena Afzal Hajni; Ajmal Anjum; Arshad Hussain; Yasir Hassan Rather; Haider Rashid (Indian Journal of Social Psychiatry)
Background: Misuse of prescription opioids has been a hazard lately with tapentadol being a recent addition to the list. Tapentadol is a schedule H1 opioid (Drugs and Cosmetics Rules, India), approved for the management of moderate-to-severe acute and chronic pain. Aims and Objectives: We examined the prevalence of tapentadol use among patients attending the Drug De-addiction Center, Government Medical College, Srinagar, Kashmir, along with their sociodemographic and clinical profiles. Materials and Methods: It was a cross-sectional study. Patients who reported current tapentadol use were included in the study. Results: In a span of 4 months, a total of 104 patients using tapentadol were seen. Our study mostly consisted of young, unmarried males. More than half of our study participants had concurrent opioid dependence. In our study, no participant had ever injected tapentadol. Conclusion: Tapentadol is becoming infamous as a cheap and ready-to-available drug, replacing other opioids during their nonavailability. This should be a potentially alarming sign for drug control authorities. As such, its sale and supply should be well regulated.